Correlations between oral Pre-Exposure Prophylaxis (PrEP) initiations and policies that enable the use of PrEP to address HIV globally - Janki Tailor; Jessica Rodrigues; John Meade; Kate Segal; Lilian Benjamin Mwakyosi (Public Library of Science (PLoS), 2022)
Policies facilitating access to HIV prevention services, specifically for pre-exposure prophylaxis (PrEP), can foster enabling environments for service uptake. This analysis aims to establish whether policies enabling broad PrEP eligibility, HIV self-testing, and lowered age of consent to HIV testing and treatment services are correlated with PrEP uptake. Ages of consent vary by country, therefore this analysis focused on how age of consent policies, in general, affect adolescent PrEP uptake. Data was collected from the HIV Policy Lab and AVAC's Global PrEP Tracker, a database of approximately 334 PrEP projects operating across 95 countries, and linear regression and correlation analyses were conducted via STATA to examine relationships amongst national oral PrEP eligibility, HIV self-testing, lowered age of consent, and national cumulative oral PrEP initiations, as of December 2021. Of all 194 countries tracked by the HIV Policy Lab, only about 7% have adopted all three policies (HIV self-testing, lowered age of consent, and PrEP eligibility policies). Less than 50% have adopted have adopted at least one of these policies. Of the 54 countries that have fully adopted PrEP eligibility policies, less than 30% have co-adopted HIV self-testing or lowered age of consent policies. About 30% of these 194 countries have yet to adopt any of these policies, of which about 14% have indicated information is "unavailable" for at least one of the policies. Analyses conducted for the 91 countries tracked by both the HIV Policy Lab and the Global PrEP Tracker revealed a significant and positive relationship between cumulative individuals initiated on oral PrEP and adoption of HIV self-testing policies (p = 0.01, r = 0.26), lowered age of consent policies (p = 0.01, r = 0.25), and PrEP eligibility policies (p = 0.01, r = 0.26). Stronger advocacy efforts towards approving public health policies, such as those outlined in our analysis, that enshrine and enable access to HIV prevention are necessary.